Explainable AI (XAI) for Fake News Detection: A Review of Interpretability in Deep Learning Models for Misinformation Classification - Munawaroh, Silvi (Universitas Komputer Indonesia, 2024)
This study provides a comprehensive review of Explainable AI (XAI) applications in fake news detection, addressing the critical